Органы размножения Erysiphe - Сорокин, Николай Васильевич; Сорокін, Микола Васильович (Харьков : В Университетской типографии, 1870)
There are the description and characterization of the microscopic fungus Erysiphe in the article.
Keywords: Общество испытателей природы; Императорский Харьковский университет; органы размножения; Erysiphe; грибок